Foot Self-Care Behaviours and the Level of Perceived Risk of Amputation in Type 2 Diabetes - Sert, Havva; Yılmaz, Feride Taşkın; Kumsar, Azime Karakoc; Öztürk, Fatma Can (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Diabetic foot which is one of the complications of diabetes may develop in parallel with the frequency of diabetes. Objective: To determine the factors affecting foot self-care behaviours and amputation risk perception levels in individuals with type 2 diabetes. Methods: The descriptive and correlational study included 157 individuals who had been diagnosed with type 2 diabetes for at least six months and had no previous diabetic foot and previous amputation history. The data were obtained by using patient diagnosis form, Foot Self-care Behaviour Scale and perceived risk of amputation evaluation form. Results: The total score of the participants from the Foot Self-Care Behaviour Scale was found to be below the mean value (37.95±8.93). It was determined that individuals, who had the disease for more than ten years and were informed on the disease, foot health and care by physician or nurse, had better foot care behaviours (p<0.05). The average amputation risk perception evaluation score was found to be very low (4.87±10.08) and 61.8% stated that they had no risk for amputation. In addition, no significant difference was found between the glycemic control parameters and the amputation risk perception levels of the individuals (p>0.05). Conclusion: It was determined that the individuals did not have good foot self-care behaviours, that disease duration and being informed on foot self-care affected foot self-care behaviours and that their amputation risk perception level was very low. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 280-288